Effects of Adding Dry Mulberry Leaves (Morusalba) in the Concentrate Diet on Digestibility and Some Blood Parameters in Female Goats (Indian Journal of Forensic Medicine & Toxicology, 2020)
This experimental study was conducted at the animal farm of the College of Veterinary Medicine ofBaghdad University during the period 15/3/2019 until 30/4/2019. Fourteen female local breed goats, ataged between 1.5–2 years and range weight 23–27kg.The animals were divided into two equal groups asfollowing G1(control) was fed on concentrate diet 2% B.W and alfa - alfa hay .G2 group was fed the samediet and 2% grinding Mulberry leaves of concentrate diet .water was offered freely. For evaluation someanimal performance. Bodyweight, some nutrients digestibility, blood picture and biochemical parameters.Results revealed that an excellent improvement was observed in body weight and nutrients digestibilitywere significantly (P
Keywords: goat, Mulberry leaves, cholesterol, performance, digestibility, leucocytes